The EU and Global Order in Transition, i.e., Civilian Power in Power Politics and the Post-Peace World - Zajączkowski, Kamil (Studia Europejskie (Warszawa), 2025)
The research subject of this article is to examine the position and signiﬁcance of the European Union within the rapidly-evolving international order, with a particular focus on the period from 2016 to 2024. The post-1989 international system is undergoing reconﬁguration, marked by dominant trends such as bilateralism, power politics, protectionism (and related economic practices), the deceleration of globalisation in favour of regionalisation (so-called “slowbalisation”), and the growing assertiveness of states such as Russia and the People’s Republic of China in international relations. In contrast, the EU represents the opposite of these trends – it is a normative and civilian power, rather than a hard power. The primary objective of this article is to address the following research questions: What are the deﬁning characteristics of the international order at the threshold of the fourth decade of the 21st century? To what degree does the EU – as both a soft and civilian power – posses the necessary instruments to shape the emerging World 2.0 which is increasingly driven by power politics?